The making of legal authority non-legislative codifications in historical and comparative perspective - Jansen, Nils. (Oxford : Oxford University Press, 2010)
From 'Justinian's Institutes' and 'Blackstone's Commentaries' to modern examples such as the 'American Law Institute's Restatements', this book offers the first comparative analysis of non-legislative codifications.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Codification; Legal literature -- History